Kewenangan Penyidik dan Penuntut Umum KPK untuk Melakukan Perampasan Aset Terdakwa yang Belum Diputus oleh Pengadilan dalam Kasus Tindak Pidana Korupsi - Pangihutan, Timothy; Sibuea, Hotma P.; Sugeng, Sugeng (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to describe the weaknesses in the regulation of asset confiscation in criminal acts of corruption in cases of defendants who have not yet received a court decision and to describe the regulation of asset confiscation of the assets of a defendant in a criminal act of corruption who dies before a decision is made in terms of the principle of separation of powers. The research method used is a normative approach method. Based on the research results, the weakness of the regulation of confiscation of assets in criminal acts of corruption in cases of defendants who have not received a court decision lies in the regulation of confiscation of state losses which is not regulated in the Corruption Crime Law, so that it is then misinterpreted as if it cannot be confiscated. Furthermore, the regulation of asset confiscation of the assets of a corruption defendant who dies before a verdict is reached must be regulated in the Corruption Crimes Law, meaning that the Corruption Eradication Commission can confiscate state losses based on the Corruption Eradication Committee investigator as prosecutor.